Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 43322 by Raj Singh last updated on 09/Sep/18

Commented by maxmathsup by imad last updated on 11/Sep/18

let A = ∫     (dx/((x+1)^2 (x^2  +1))) let decompose F(x) = (1/((x+1)^2 (x^2  +1)))  F(x) = (a/(x+1)) +(b/((x+1)^2 )) +((cx +d)/(x^2  +1))  b =lim_(x→−1) (x+1)^2 F(x) =(1/2)  lim_(x→+∞)  xF(x) =0 =a+c ⇒c =−(1/2) ⇒F(x) =(a/(x+1)) +(1/(2(x+1)^2 )) +((−(1/2)x +d)/(x^2  +1))  F(o) =1 = a +(1/2) +d ⇒ a+d =(1/2)  F(2) =(1/(45)) = (a/3) +(1/(18)) +((d−1)/5) ⇒ 1 =15a +((45)/(18))  +9d−9 ⇒  1 =15a +(5/2) +9d−9 ⇒15a +9d =10−(5/2) =((15)/2) ⇒  15a +9((1/2)−a)=((15)/2) ⇒6a =((15)/2) −(9/2) =3 ⇒a=(1/2) ⇒d=0 ⇒  F(x)= (1/(2(x+1))) +(1/(2(x+1)^2 )) −(x/(2(1+x^2 ))) ⇒  A = ∫ F(x)dx =(1/2)ln∣x+1∣ −(1/(2(x+1))) −(1/4)ln(1+x^2 ) +c .

letA=dx(x+1)2(x2+1)letdecomposeF(x)=1(x+1)2(x2+1)F(x)=ax+1+b(x+1)2+cx+dx2+1b=limx1(x+1)2F(x)=12limx+xF(x)=0=a+cc=12F(x)=ax+1+12(x+1)2+12x+dx2+1F(o)=1=a+12+da+d=12F(2)=145=a3+118+d151=15a+4518+9d91=15a+52+9d915a+9d=1052=15215a+9(12a)=1526a=15292=3a=12d=0F(x)=12(x+1)+12(x+1)2x2(1+x2)A=F(x)dx=12lnx+112(x+1)14ln(1+x2)+c.

Answered by tanmay.chaudhury50@gmail.com last updated on 09/Sep/18

2)∫(dx/((x+1)^2 (x^2 +1)))  ∫(a/((x+1)))dx+∫(b/((x+1)^2 ))dx+∫((cx+d)/(x^2 +1))dx  now calculating a b c and d  (1/((x+1)^2 (x^2 +1)))=(a/(x+1))+(b/((x+1)^2 ))+((cx+d)/(x^2 +1))  1=a(x+1)(x^2 +1)+b(x^2 +1)+(cx+d)(x+1)^2    1=a(x^3 +x^2 +x+1)+b(x^2 +1)+(cx+d)(x^2 +2x+1)  1=a(x^3 +x^2 +x+1)+b(x^2 +1)+(cx^3 +2cx^2 +cx+dx^2 +2dx+d)  1=x^3 (a+c)+x^2 (a+b+2c+d)+x(a+c+2d)+(a+b+d)  a+c==0  a+b+2c+d=0    a+c+2d=0  a+b+d=1  a+c+d=0  0+d=0  d=0  a+b=1  a+b+2c+d=0  1+2c+0=0  c=((−1)/2)     a+c=0   a=−c  a=(1/2)   a=(1/2)   a+b=1   b=(1/2)   c=((−1)/2)   d=0  ∫(a/(x+1))dx+∫(b/((x+1)^2 ))+∫((cx)/(x^2 +1))dx  (1/2)∫(dx/(x+1))+(1/2)∫(dx/((x+1)^2 ))  + ((−1)/2)∫(dx/(x^2 +1))  (1/2)ln(x+1)+(1/2)×(((x+1)^(−1) )/(−1))−(1/2)tan^(−1) (x)+c  (1/2)ln(x+1)−(1/(2(x+1)))−(1/2)tan^(−1) (x)+c

2)dx(x+1)2(x2+1)a(x+1)dx+b(x+1)2dx+cx+dx2+1dxnowcalculatingabcandd1(x+1)2(x2+1)=ax+1+b(x+1)2+cx+dx2+11=a(x+1)(x2+1)+b(x2+1)+(cx+d)(x+1)21=a(x3+x2+x+1)+b(x2+1)+(cx+d)(x2+2x+1)1=a(x3+x2+x+1)+b(x2+1)+(cx3+2cx2+cx+dx2+2dx+d)1=x3(a+c)+x2(a+b+2c+d)+x(a+c+2d)+(a+b+d)a+c==0a+b+2c+d=0a+c+2d=0a+b+d=1a+c+d=00+d=0d=0a+b=1a+b+2c+d=01+2c+0=0c=12a+c=0a=ca=12a=12a+b=1b=12c=12d=0ax+1dx+b(x+1)2+cxx2+1dx12dxx+1+12dx(x+1)2+12dxx2+112ln(x+1)+12×(x+1)1112tan1(x)+c12ln(x+1)12(x+1)12tan1(x)+c

Terms of Service

Privacy Policy

Contact: info@tinkutara.com